Experience with the Postgraduate Mining Geomechanics Course by Correspondence at the University of New South Wales School of Mines (The Australasian Institute of Mining and Metallurgy, 1986)
A Master of Applied Science degree course in Mining Geomechanics commenced in 1983 at The University of New South Wales, taught by extern- al (correspondence) studies. The course is aimed at graduates employed in the mining indust- ry, and especially people involved in geomechan- ics projects on a routine basis in remote locations. This kind of course is unique in Australia and is one of only two correspondence programmes available at this University. The author designed the course and nursed it through the early years, and was Director until 1986. The paper describes the teaching and assess- ment methods and also discusses aspects of admin- istration and coordination of such a course. It is concluded that an important need of the mining industry is being catered for and it appears that similar correspondence course for- mats would also be useful in other areas of the minerals industry.